2018
DOI: 10.12659/msm.908251
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Evaluation of the Cortisol Response to Cardiac Surgery with Occurrence of Early Postoperative Cognitive Decline

Abstract: BackgroundA recent study reported that patients with higher cortisol levels on the 1st postoperative morning after cardiac surgery exhibited an increased risk of early postoperative cognitive decline (POCD). Therefore, we conducted the current study to gain further insight into the stress response to a surgical procedure as a potential risk factor for early POCD after cardiac surgery.Material/MethodsThis prospective cohort study enrolled 125 patients undergoing elective cardiac surgery with or without cardiopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
1
11
0
2
Order By: Relevance
“…Glumac et al. 26 revealed that the stress response to surgical procedures is unlikely to represent an exclusive trigger for the occurrence of POCD and that interdependent mechanisms, such as inflammatory and stress responses, may be involved in the pathogenesis of POCD through their interaction effects. In the present study, we evaluated different operations performed by different surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Glumac et al. 26 revealed that the stress response to surgical procedures is unlikely to represent an exclusive trigger for the occurrence of POCD and that interdependent mechanisms, such as inflammatory and stress responses, may be involved in the pathogenesis of POCD through their interaction effects. In the present study, we evaluated different operations performed by different surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…The opposite results reached S. Glumac et al [18] in a prospective cohort study of patients who underwent planned heart surgery. Cortisol levels were determined the day before surgery, 1 day after surgery (08-00, 16-00 and 24-00), for 3 and 5 days.…”
Section: Discussion Of Research Resultsmentioning
confidence: 85%
“…The studies showed that high serum cortisol levels can predict adverse outcome in patients with severe community acquired pneumonia, cardiac event risk in chronic heart failure, survival state in resuscitated cardiopulmonary arrest, mortality risk in chronic haemodialysis, and development of postoperative cognitive dysfunction following cardiac surgery. (9)(10)(11)(12)(13)(14)(15) To our knowledge, this is the first study to investigate the association between cortisol levels and surgical abdominal pain. It's an important problem to estimate surgical disease in patients with abdominal pain, especially at the early stage of 21) NLR is a predictor of acute inflammation and was recently studied in many clinical conditions for the diagnosis or prognosis.…”
Section: Discussionmentioning
confidence: 96%